Computational simulation of the mechanobiological response of arterial tissue - Boyle, Colin James (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2012)
Ischaemic heart disease, causing restriction of arterial blood flow to the heart tissue, can be treated with mechanical revascularisation treatments such as balloon angioplasty and stent implantation. One remaining limitation to the success of these treatments in the re-blockage of the treated artery, termed restenosis. The paradigm of re-blockage as the tissue's response to injury has been proposed to explain restenosis in stents and corroborated with pathological studies, this paradigm has never been used to form the basis of a predictive theoretical model of restenosis. In this thesis, the hypothesis that mechanically-induced injury stimulates restenosis is tested by developing a simulation technique based on this paradigm. The model explicitly simulates the response of individual cells to injury-induced inflammation.
Keywords: Mechanical Engineering, Ph.D.; Ph.D. Trinity College Dublin